Malaysian studies - Mardiana Nordin (Oxford Fajar, 2011)
Malaysian Studies has been developed as the main resource book for private institution students for the course (LAN 1003) at Diploma and Bachelor degree levels. This book can also be used by public institution students as well as all Malaysian citizens who wish to find out more about the country from its conception to date. It is hoped that the knowledge gained from using this book will be beneficial in terms of producing a citizen who is solid, proud and patriotic. The book contains 16 chapters, covering all the main themes in the syllabus, including historical aspects; administration systems and law; the nation's principles; socioeconomic growth and development; and community spirit, as well as current issues affecting the country today. The book also contains three additional chapters, namely 'Malaysia in the Globalisation Era'; '1Malaysia'; and 'Development of the Role Model Malaysian'. Current issues are discussed and debated in these topics.